2022
DOI: 10.52131/pjhss.2022.1001.0209
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Students’ Academic Self-Concept in English as Predictor of Their Academic Performance

Abstract: The main concern of the current work was to analyze the academic self-concept (ASC) of students in English as a predictor of their performance. For this purpose, overall, 288 students representing both genders enrolled in grade 10 were the respondents of the study. A Likert scale method was administered to find students’ extent of academic self-concept to further correlate it with their obtained marks in English in the final exam of the 9th class. A demographic-based analysis was conducted under both descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…It was concluded that academic self-concept is related to academic achievement (Zahra, Asif, & Yousaf, 2010). Similarly, another study demonstrated that both selfconcept and academic achievement complement each other also among students at higher education levels (Deeba & Shah, 2016). So, this research study is of paramount importance in exploring the relationship between two variables in our cultural context and then employing the findings for the betterment of the academic as well as non-academic life of our youth.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…It was concluded that academic self-concept is related to academic achievement (Zahra, Asif, & Yousaf, 2010). Similarly, another study demonstrated that both selfconcept and academic achievement complement each other also among students at higher education levels (Deeba & Shah, 2016). So, this research study is of paramount importance in exploring the relationship between two variables in our cultural context and then employing the findings for the betterment of the academic as well as non-academic life of our youth.…”
Section: Introductionmentioning
confidence: 73%
“…At this time, the identifications of earlier childhood will be re-shaped or discarded to resolve confusion and fragmentation about the self (McAdams, 2010), and individuals move towards the creation of a stable and positive self-concept to support the transition to adulthood. The self-concept among the students is also found in Pakistani literature to be associated with academic achievement (Deeba & Shah, 2016;Zahra et al, 2010). The aforementioned research also indicates that feedback from significant others greatly influences the self-concept (Manning, 2007) and teachers hold a significant position in a student's life.…”
Section: Introductionmentioning
confidence: 89%
“…It is worth mentioning that this questionnaire has been previously used in research conducted by Martínez et al [27], García Ponce and Gómez-Mármol [28] and Huamán-Chura [29]. Additionally, Deeba, Saleem and Ulla [30] used a Likert scale method to find students' extent of academic self-concept to further correlate it with their obtained marks in English.…”
Section: Data Collection Instrumentsmentioning
confidence: 99%
“…Su has effectively improved the data processing algorithm on the basis of machine learning and neural network algorithm to improve the accuracy of learning achievement prediction [14]. To improve students' academic performance, Deeba et al analyzed the self-concept of English majors in detail, thus providing help for improving students' self-concept and achieving effective prediction of performance [15].…”
Section: Introductionmentioning
confidence: 99%